Effects of shear strength reduction strategies on safety factor of homogeneous slope based on a general nonlinear failure criterion. (January 2015) - Zhao, Lianheng; Yang, Feng; Zhang, Yingbin; Dan, Hancheng; Liu, Weizheng
Abstract: Safety factor of slope is often calculated based on the conventional linear Mohr–Coulomb failure criterion. However, many experimental results show that the strength envelopes of almost all of geomaterials are characteristically nonlinear. This paper presents a method (upper bound limit analysis method) to analyze the stability of a homogeneous slope based on a general nonlinear failure criterion, in which different shear strength reduction strategies (SSRS ) can be used. Based on the presented method, three SSRSs (i.e. by factoring the unconfined shear strength c 0 only, by factoring the tensile strength σt only, by factoring both the unconfined shear strength c 0 and the tensile strength σt ) are used to calculate the safety factors of a homogeneous slope under a general nonlinear failure criterion. Compared results show different SSRSs have significant influence on the calculated safety factor.